High school students from public schools in Fortaleza-CE and the interest in Botany (Research, Society and Development, 2021)
Botany studies and classifies plants considering their forms, structures, and composition; its knowledge is closely associated with people's daily lives. However, its presence is almost always ignored, so that, in Basic Education, it is seen as a very theoretical, descriptive, and discouraging content. Therefore, it is important to know the student's opinion about the subject and try to promote improvements in this area. Thus, this study aimed to investigate the interest in Botany of high school students from two public schools in Fortaleza. To this end, a questionnaire was applied to 71 2nd year high school students from two public high schools in Fortaleza, composed of seven questions, asking them about the difficulties they encounter, the way their teachers share the content, suggestions to improve their understanding of the subject, among others. The Biology teachers of the respective classes also participated in the research, to find out their opinion on the subject and their performance in the classroom. It was verified that most students are interested in Botany and find it relevant to know about the subject, however, they present some difficulties, especially regarding nomenclature, so that the teacher has a fundamental role in facilitating the understanding of this content.